1995
DOI: 10.2151/jmsj1965.73.6_1087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Mean Summer Monsoon Flow and 45-Day Transient Perturbations

Abstract: The influence of the low-level mean summer monsoon flow on 45-day transient eddies through barotropic interaction is diagnosed by a scalar product between the horizontal shear vector and Eliassen-Palm (E-P) flux, while the dry (moist) baroclinic interaction is measured by a vector product between the vertical wind shear and the eddy sensible (latent) heat transport, which represents the vertical component of E-P fluxes. Activity of 45-day transient eddies was monitored by the evolution of kinetic energy during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…2c). This eastward shift from June-July through August is similar to the shift for MJO-scale eddies demonstrated by Kawamura and Murakami (1995).…”
Section: Differences In Transient Disturbancesupporting
confidence: 80%
See 4 more Smart Citations
“…2c). This eastward shift from June-July through August is similar to the shift for MJO-scale eddies demonstrated by Kawamura and Murakami (1995).…”
Section: Differences In Transient Disturbancesupporting
confidence: 80%
“…Kawamura and Murakami (1995) investigated the role of the deformed mean tropical and extratropical westerlies on eddy growth for MJO-scale tropical disturbances. They showed that stretching and shearing deformation in the exit region of the monsoon westerlies (in the tropics) supplies barotropic energy to the MJO-scale eddies.…”
Section: Dynamical Interaction Between Transient Eddies and The Mean mentioning
confidence: 99%
See 3 more Smart Citations